Analysis the Expected Profit By the Relation Between the Sustainable growth and Actual growth: Apply Study for Iraq Stock Exchange (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The research aims to analysis the future profits of companies listed on the Iraq Stock Exchange through analyzing the relationship between Actual Growth and Sustainable Growth, The study was applied to the sample of companies included in the Iraq Stock Exchange for the period (2010- 2014), The Internal Growth Rate has been used as a measure for the Actual Return Rate but the Sustainable Growth Rate has been measured under the Rose model, The research showed group of conclusions, the most important are:1. From the analysis of sustainable growth for the banks sample and the variables involved in its measure shows that investment in the investors amounts have achieved a significant return, which demonstrates the company's efficiency at generating profits from every unit of shareholders' equity.2. From the analysis of the Rate of Equity (ROE) and there is a clear vision for the investor in the stock for comparison among companies showing through the height of this index for banks research sample so whenever the less value of this ratio means it is bad for the company's performance indicator, the higher of this ratio for a long time is indicated good company's management, as well as the back of low internal growth from equity fluctuation this refers to drop the bank's dependence on external sources to finance their investments.Keyword: Actual Growth Rate (AGR), Sustainable Growth Rate (SGR), Internal Rate of Return (IRR), Return on Equity (ROE), Return of Investment (ROI).